Cultural Influence on Clinical Features of Depression - Gani, Rina Krismiati; Mahajudin, Marlina Setiawati; Budi Kristianto (Jurnal Psikiatri Surabaya, 2022)
Introduction: Depression is a common cause of poor health throughout the world. Genotype factors and cultural environment will interact to influence the psychodynamics of a person's behavior in expressing depression. Objective: This paper aims to describe the influence of cultural factors on a person's psychodynamics and clinical features of depression. Methods: PubMed and Google Scholar were searched using the following keyword (depression) AND (clinical features OR clinical appearance) AND (psychodynamic) AND (cultural influences) using the journal publication filter for the 2014-2020 issues. We also used textbooks published in the last 10 years and were related to writing themes. Results: Every individual has "internal” and "external” views within him, which are influenced by the culture in which he grows and develops. These views, along with beliefs, religions, and gender differences can influence the type and severity of depression as well as variations in clinical appearance. In addition, most of the existing psychometrics developed in Europe and the United States, so some items are not appropriate when applied in different cultures. In Indonesia, there is an Indonesian Depression Checklist that has been adapted to Indonesian culture to detect depression. Physicians must avoid stereotyping members of certain cultural groups while respecting the importance of cultural influences. Conclusions: Psychodynamics and culture will influence behavior in response to the distress, resulting in clinical vary features of depression across cultures. Healthcare workers must have the cultural competence to sharpen their analytical power and avoid misdiagnosis of depression.